2015
DOI: 10.1039/c4ra13266a
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the mechanical and morphological properties of self-assembled peptide hydrogels via control over the gelation mechanism through regulation of ionic strength and the rate of pH change

Abstract: Hydrogels formed by the self-assembly of peptides are promising biomaterials. The bioactive and biocompatible molecule Fmoc-FRGDF has been shown to be an efficient hydrogelator via a p-b self-assembly mechanism. Herein, we show that the mechanical properties and morphology of Fmoc-FRGDF hydrogels can be effectively and easily manipulated by tuning both the final ionic strength and the rate of pH change. The increase of ionic strength, and consequent increase in rate of gelation and stiffness, does not interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 37 publications
7
49
0
Order By: Relevance
“…[7,15] Fibril structures have been reported as the main morphological structure of relativelys trong gels. [7,15,[35][36][37][38][39][40] Redox triggering in compounds is anovel and significant property.T here are al imited number of compounds that show redox reversibility,e xamples include af errocenemodified phospholipid in redox-triggered drug-delivery vesicles reported by Noyhouzer et al [41] Miao et al also exhibited redox-controlled self-assembling peptides. [42] Redox-responsive supramolecular polymers can also be used as smart carriers for controllable drug or protein delivery in tissues.…”
Section: Morphological Investigationmentioning
confidence: 99%
“…[7,15] Fibril structures have been reported as the main morphological structure of relativelys trong gels. [7,15,[35][36][37][38][39][40] Redox triggering in compounds is anovel and significant property.T here are al imited number of compounds that show redox reversibility,e xamples include af errocenemodified phospholipid in redox-triggered drug-delivery vesicles reported by Noyhouzer et al [41] Miao et al also exhibited redox-controlled self-assembling peptides. [42] Redox-responsive supramolecular polymers can also be used as smart carriers for controllable drug or protein delivery in tissues.…”
Section: Morphological Investigationmentioning
confidence: 99%
“…The positively charged lysine groups attract negatively charged chloride ions from solution, which themselves attract further lysine groups attached to other fibrils. This increased electrostatic interaction enables stronger supramolecular interactions between the aligned fibrils, increasing the effective points of entanglement and resulting in a more rigid nanofibrous network [31].…”
Section: Materials Characterization Of the Lysinefunctionalized Self-amentioning
confidence: 99%
“…2016, 9(3): 674-684 microns in length, that orientate themselves longitudinally into a network of interconnected bundles, forming a structural mimetic of the extracellular matrix [30]. We have shown that the mechanical properties of these Fmoc-SAPs can be easily tailored for tissue-specific applications through adjustment of the rate of assembly as well as the ionic concentration, without disturbing the nanofibrous morphology [31]. The biocompatibility of Fmoc-SAPs has been demonstrated across a range of sequences, and we have shown that optimal biocompatibility and functionality of the Fmoc-SAPs requires the incorporation of bioactive peptide sequences [30,[32][33][34].…”
Section: Introductionmentioning
confidence: 95%
“…[44] A stimulus is required to initiate assembly, and must be presented as uniformly as possible to ensure homogeneity, and the rate at which the stimulus (heat, ionic strength, pH) is applied must be adjusted to promote ordered structures and avoid uncontrolled aggregation or precipitation. [46,44] The catalytic action of enzymes has also been used to modify these interactions due to the formation/cleavage of bonds. For biological applications, it is important that the molecular assembly occurs under physiological conditions (pH 7.4, salt concentration 150 × 10 −3 m, and temperature 37 °C) to ensure that the desirable hydrogel structure is retained in vivo [47] An important and often overlooked property is that the final material is optically transparent, as a significant number of cell assays utilize fluorescent dyes.…”
Section: Hydrogel Materialsmentioning
confidence: 99%